2014
DOI: 10.1530/eje-14-0147
|View full text |Cite
|
Sign up to set email alerts
|

Serum negative autoimmune thyroiditis displays a milder clinical picture compared with classic Hashimoto's thyroiditis

Abstract: Background: Despite high sensitivity of current assays for autoantibodies to thyroperoxidase (TPO) and to thyroglobulin (Tg), some hypothyroid patients still present with negative tests for circulating anti-thyroid Abs. These patients usually referred to as having seronegative autoimmune thyroiditis (seronegative CAT) have not been characterized, and definite proof that their clinical phenotype is similar to that of patients with classic chronic autoimmune thyroiditis (CAT) is lacking. Objective: To compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…These relevant differences presumably reflect differences in study design (prospective vs retrospective), characteristics of the studied populations, and clinical criteria used to adjust L- In the present study, the positivity of anti-thyroid autoantibodies and, consistently, the autoimmune origin of hypothyroidism resulted statistically significantly associated with the need for L-T 4 adjustment in early pregnancy, indicating that the contribution of the thyroid gland to the maintenance of euthyroidism is further impaired and becomes insufficient during pregnancy. This significant association and the high prevalence (50%) of TAI-negative hypothyroidism in the group of patients who did not need to adjust L-T 4 dosage in early pregnancy indirectly support the thesis of a milder clinical course of TAI-negative hypothyroidism when compared with autoimmune hypothyroidism (22). Finally, it has to be emphasized that only one of the ten studies shown in Table 1 reported data separately for assisted reproductive technology (ART) pregnancies (15), and we cannot exclude that data from other contributions may have been inflated by the inclusion of some IVF pregnancies.…”
Section: Clinical Study a Busnelli And Others Levothyroxine Adjustmenmentioning
confidence: 75%
“…These relevant differences presumably reflect differences in study design (prospective vs retrospective), characteristics of the studied populations, and clinical criteria used to adjust L- In the present study, the positivity of anti-thyroid autoantibodies and, consistently, the autoimmune origin of hypothyroidism resulted statistically significantly associated with the need for L-T 4 adjustment in early pregnancy, indicating that the contribution of the thyroid gland to the maintenance of euthyroidism is further impaired and becomes insufficient during pregnancy. This significant association and the high prevalence (50%) of TAI-negative hypothyroidism in the group of patients who did not need to adjust L-T 4 dosage in early pregnancy indirectly support the thesis of a milder clinical course of TAI-negative hypothyroidism when compared with autoimmune hypothyroidism (22). Finally, it has to be emphasized that only one of the ten studies shown in Table 1 reported data separately for assisted reproductive technology (ART) pregnancies (15), and we cannot exclude that data from other contributions may have been inflated by the inclusion of some IVF pregnancies.…”
Section: Clinical Study a Busnelli And Others Levothyroxine Adjustmenmentioning
confidence: 75%
“…In the study by Rotondi et al. [25], it was revealed that antibody‐negative HT patients have a milder clinical course, with less overt hypothyroidism, as compared to antibody‐positive patients. Therefore, the poor HRQoL of euthyroid patients with a positive antibody makes it obvious that thyroid antibodies are the markers for the consequent systemic autoimmune disease development with numerous symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…If thyroid destruction would mainly be mediated by comple-ment-binding humoral immunity, a clear correlation between TSH and thyroid Abs would be expected, which has not been seen. Additionally, the existence of seronegative AIT patients [36], which are defined as TSH elevation with histologically proven leukocytic infiltration without thyroid Abs appearance, supports this concept. In summary, our data indicate largely elevated levels of TPO-Abs being associated with a moderately increased risk of developing hypothyroidism.…”
mentioning
confidence: 75%